E-learning theory and practice - Haythornthwaite, Caroline A.; Andrews, Richard, 1953 April 1- (Los Angeles : Sage, 2011)
In 'E-learning Theory and Practice', the authors set out different perspectives on e-learning. The book deals with the social implications of e-learning, its transformative effects, and the social and technical interplay that supports and directs e-learning.
The new media -- Theories of learning -- Theorizing online learning -- New literacies, new discourses in e-learning -- Participatory cultures -- Learning communities -- Sociotechnical perspectives -- E-learning ecologies -- Ubiquitous learning, ubiquitous learners -- E-inclusion and exclusion -- Cross-cultural issues -- Researching e-learning.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Internet in education; Computer-assisted instruction; Web-based instruction -- Social aspects; Internet -- Study and teaching; Electronic books